Cover Image, Volume 39, Issue 2. Issue 2 (10th January 2018) - Signorino, Giulia; Covaceuszach, Sonia; Bozzi, Manuela; Hübner, Wolfgang; Mönkemöller, Viola; Konarev, Petr V.; Cassetta, Alberto; Brancaccio, Andrea; Sciandra, Francesca
Abstract : On the cover : This cover image, by Giulia Signorino et al., is based on the Research Article A dystroglycan mutation (p.Cys667Phe) associated to muscle‐eye‐brain disease with multicystic leucodystrophy results in ER‐retention of the mutant protein, Pages 266–280. DOI:10.1002/humu.23370 .